(untitled) (Archive of Conferences, 2021)
Preeclampsia is currently one of the leading causes of death and severe maternal morbidity. Although its prevalence is still underestimated in some places due to underreporting, preeclampsia is a medical condition that healthcare professionals need to know how to deal with and respond to. For this reason, research on a topic stays with progress in understanding it, which often implies improvements and changes in concepts and behavior